Al-Ghazali's Thoughts on Education and Its Relevance to Islamic Education in the Millennial Era - Guntur Gunawan; Ayunia Lestari (AJIS: Academic Journal of Islamic Studies, 2021)
This article aims to describe and critically analyze the thoughts of Islamic education according to al-Ghazali, especially regarding the objectives, sources, methods, and curriculum and their relevance to the world of Islamic education in the millennial era. This research uses library research method, with character thinking approach. This study found that; First, al-Ghazali's thoughts on Islamic education are (a) the Qur'an and Hadith are the main foundations of education; (b) getting closer to Allah is the main intention of educators, then acting as an example for their students, and being competent in teaching; (c) the students must stay away from immorality, respect teachers and study diligently by exploring the lessons given by the teacher; (d) the curriculum as an educational tool must be adapted to the development of students; (e) students must be kept away from bad associations, because a bad environment will affect the development of the students, especially in the family, school or community environment. Second, al-Ghazali's thought has relevance to Islamic education in this millennial era, when viewed from the compatibility between al-Ghazali's educational theory and things that have been applied in the world of education.